Two new species of Charidotella Weise (Coleoptera: Chrysomelidae: Cassidinae: Cassidini), with a key to Charidotella sexpunctata group - Borowiec, Lech (Zootaxa, 2007)
Two new species of Charidotella s. str. are described: Charidotella moraguesi from French Guyana and Charidotella pacata from Bolivia and Brazil. Both belong to the group of species close to Charidotella sexpunctata Fabricius characterized by a dark pattern on the ventral surface of elytral disc. A key to the Charidotella sexpunctata group is given.